A Genetic Resource for Rice Improvement: Introgression Library of Agronomic Traits for All AA Genome Oryza Species - Zhang, Yu; Zhou, Jiawu; Xu, Peng; Li, Jing; Deng, Xianneng; Deng, Wei; Yang, Ying; Yu, Yanqiong; Pu, Qiuhong; Tao, Dayun (Frontiers in Plant Science, 2022)
Rice improvement depends on the availability of genetic variation, and AA genome Oryza species are the natural reservoir of favorable alleles which are useful for rice breeding. To systematically evaluate and utilize potentially valuable traits of new QTLs/genes for the Asian cultivated rice improvement from all AA genome Oryza species, 6372 agronomic trait introgression lines (ILs) from BC2 to BC6 were screened and raised based on variations of agronomic traits by crossing 170 accessions of 7 AA genome species and 160 upland rice accessions of O. sativa as the donor parents, with three elite cultivars of O. sativa, Dianjingyou 1 (a japonica variety), Yundao 1 (a japonica variety) and RD23 (an indica variety) as the recurrent parents, respectively. The agronomic traits, such as spreading panicle, erect panicle, dense panicle, lax panicle, awn, prostrate growth, plant height, pericarp color, kernel color, glabrous hull, grain size, 1,000-grain weight, drought resistance and aerobic adaption, blast resistance, were derived from more than one species. Further, 1,401 agronomic trait ILs in the Dianjingyou 1 background were genotyped using 168 SSR markers distributed on the whole genome. Twenty-two novel allelic variations were identified to be highly related to the traits of grain length and grain width respectively. In addition, allelic variations for the same locus were detected from the different donor species, suggesting that these QTLs or genes were conserved and the different haplotypes of a QTL (gene) were valuable resources for broadening the genetic basis in Asian cultivated rice. Thus, this agronomic trait introgression library from multiple species and accessions provided the powerful resource for future rice improvement and genetic dissection of agronomic traits.